2017
DOI: 10.18805/ijar.b-3346
|View full text |Cite
|
Sign up to set email alerts
|

Mice pathology study of toxA and exoS genes bearing Pseudomonas aeruginosa isolated from bovine Sub-clinical mastitis in West Begal with their Antibiogram

Abstract: Sub-clinical Mastitis is one of the major problems in India which is among the largest milk producing countries in the world, hampering national economy. Among 422 bovine milk samples screened from different cattle farms of West Bengal with history of infection and drop in milk yield by on-spot bromothymol blue (BTB) test, 371 samples were considered for collection and secondary screening by somatic cell count study. The collected milk samples showed significantly high average SCC value of 3.26-4.88 lakh cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…While few studies have reported the isolation of P. aeruginosa from milk samples with subclinical mastitis in our country, the isolation rate has varied between 1.1% and 7.9% (Sahin and Erbas, 2015;Tel et al, 2009;Ozturk et al, 2019). In the previous studies, conducted in the world, the isolation rate has been reported as 6.5% (Banerjee et al, 2017) in India, 26.6% (Neamah et al, 2017) in Iraq, and 34% in Iran (Mokhtari et al, 2016). These differences in isolation rates may be due to regional variations and differences between isolation methods.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…While few studies have reported the isolation of P. aeruginosa from milk samples with subclinical mastitis in our country, the isolation rate has varied between 1.1% and 7.9% (Sahin and Erbas, 2015;Tel et al, 2009;Ozturk et al, 2019). In the previous studies, conducted in the world, the isolation rate has been reported as 6.5% (Banerjee et al, 2017) in India, 26.6% (Neamah et al, 2017) in Iraq, and 34% in Iran (Mokhtari et al, 2016). These differences in isolation rates may be due to regional variations and differences between isolation methods.…”
Section: Discussionmentioning
confidence: 93%
“…Neamah (2017) reported that the toxA gene was detected in 100% of strains while the exoS gene was in 75% of P. aeruginosa isolates isolated from the milk of cows with mastitis. Banerjee et al (2017) detected the toxA gene at a rate of 63.2% and the exoS gene at a rate of 36.8%. Similar to these studies (Banerjee et al, 2017;Neamah et al, 2017), many studies including virulence factors such as toxA and exoS have generally been reported at high rates and have supported the data of our study.…”
mentioning
confidence: 98%
See 2 more Smart Citations